What is the sensitivity and specificity of urinary antigen tests to identify sexually transmitted infections?. Issue 5 (May 2018) - Yang, Ryan; Xiong, Lesley
Abstract : EVIDENCE‐BASED ANSWER : The lateral flow immunoassay urinary antigen tests for chlamydia have a sensitivity between 41% and 88% and a specificity between 89% and 99% (SOR: A, meta‐analysis of cohort studies). The immunoassay urinary antigen test for gonorrhea has a sensitivity of 100% and a specificity between 93% and 98% (SOR: B, systematic review of cohort studies).